PENGARUH PEMAHAMAN KARYAWAN ATAS PERHITUNGAN, PEMOTONGAN DAN PELAPORAN PAJAK PENGHASILAN ORANG PRIBADI DALAM NEGERI TERHADAP KETAATAN DALAM PERPAJAKAN PADA PT.GAG NIKEL - Martha Carolina (Jurnal Akuntansi Bisnis, 2017)
Based on the results of research done on the PT Gag Nikel, its appears that there are still many employees above of non – taxable income does not understand how to calculate and report income tax an individual taxpayer. Based on this the authors make the point as follows "What is the understanding of employees on the calculation and reporting of personal income tax in the country to obedience in the taxation of PT Gag Nikel". The research method used was quantitative research methods. Methods of data collection using a literature study and field study. While the quantitative data analysis using statistics. From the description of the recapitulation of the indicator is known that the employees of PT Gag Nikel understanding of the calculation, withholding and reporting of personal income tax interpretation of the figure 4.08. Based on a predetermined interval scale of this figure is included in the category of "Good". This indicated that the employees of PT Gag Nikel know the calculation, withholding and reporting of personal income tax in the country.While the results summary indicator of compliance employees of PT Gag Nikel interpretation of the tax rate of 4.24 is obtained. Based on a predetermined interval scale of this figure belongs to the category "Good". This indicated that the employees of PT Gag Nikel follow the rules of taxation on personal income taxes in the country.Keywords: report income tax an individual taxpayer, calculation, withholding and reporting of personal income tax interpretation